The Socialization of L2 Doctoral Students through Written Feedback. Issue 2 (4th March 2021) - Anderson, Tim
ABSTRACT: This study examined the role of written feedback in the academic discourse socialization of second language doctoral students at a Canadian research university. Using a second language socialization framework, and foregrounding the sociocultural and interactional contexts of language learning and use, this article considers written feedback to be a form of social practice that socializes students and discursively positions them into a range of identity categories, academic discourse practices, and communities. Data sources include interviews, student-produced narratives, and written feedback artifacts. The analysis focuses on the students' interpretations of, responses to, and stated preferences and dispreference towards the feedback they received. Findings reveal that feedback played a formative role in their broader socialization and contributed to the co-construction of academic identities and (in)access to preferred discourse practices in their departments and disciplines.